Vaccine Development against Zoonotic Hepatitis E Virus: Open Questions and Remaining Challenges - Nan, Yuchen; Wu, Chunyan; Zhao, Qin; Sun, Yani; Zhang, Yan-Jin; Zhou, En-Min (Frontiers in Microbiology, 2018)
Hepatitis E virus (HEV) is a fecal-orally transmitted foodborne viral pathogen that causes acute hepatitis in humans and is responsible for hepatitis E outbreaks worldwide. Since the discovery of HEV as a zoonotic agent, this virus has been isolated from a variety of hosts with an ever-expanding host range. Recently, a subunit HEV vaccine developed for the prevention of human disease was approved in China, but is not yet available to the rest of the world. Meanwhile, notable progress and knowledge has been made and revealed in recent years to better understand HEV biology and infection, including discoveries of quasi-enveloped HEV virions and of a new function of the HEV ORF3 product. However, the impact of these new findings on development of a protective vaccine against zoonotic HEV infection requires further discussion. In this review, hallmark characteristics of HEV zoonosis, the history of HEV vaccine development, and recent discoveries in HEV virology are described. Moreover, special attention is focused on quasi-enveloped HEV virions and the potential role of the HEV ORF3 product as antibody-neutralization target on the surface of quasi-enveloped HEV virions to provide new insights for future development of improved vaccines against zoonotic HEV infection.